Wood Dust Exposure as a Risk Factor for Respiratory Disorders in Furniture Workers: A Systematic Review - Irhamna, Nada Adinda (Tadulako University, 2025)
Wood dust is generated when machines are used to cut, shape, or smooth wood materials. One industry that has a high risk of exposure to wood is the furniture industry. Wood dust particles can enter the lungs and affect respiratory health when inhaled. The study aims to determine wood dust exposure and explain the risk factors for respiratory disorders in furniture workers. The method used was literature review. This review process includes several stages, starting from identification using keywords, screening titles and abstracts, determining article eligibility, selection based on inclusion criteria, to data extraction. The articles analyzed in this review came from the period 2019 to 2024, with a total of seven articles reviewed. The results of statistical analysis in each study showed that the p-value was <0.05, indicating that wood dust exposure is considered a significant risk factor for respiratory disorders of furniture workers. The results of this systematic review indicate the need for increased awareness and compliance with the use of PPE among workers.